Pemanfaatan Berkelanjutan Limbah Anggur melalui Uji Fitokimia dan Bioaktivitas untuk Pemakaian Nutraseutik Biji dan Kulit yang Dikeringkan di Bawah Sinar Matahari: Sustainable Utilization of Grapevine Waste as a Nutraceutical - Ghosh, Somali; Kalpana, Chinnappan A (Amerta Nutrition, 2025)
Background: Grape (Vitis vinifera L.), a widely cultivated fruit, generates substantial waste during wine production. Traditionally discarded, this waste was reviewed for various applications, including chemicals, bio-products, and pigments. Objectives: Sundried seeds (SDS) and peel (SDP) of grapes (Vitis vinifera L.) were investigated for phytochemical composition and potential bioactivity as waste material for potential health benefits. Methods: Grapevine waste, specifically seeds and peel, was sun-dried and employed for the experimental study with convenient sampling for quantitative analysis. The dried samples were subjected to Fourier-transform infrared (FTIR) spectroscopy to identify primary and secondary metabolites. Ultraviolet-visible (UV-Vis) spectrophotometry was used to quantify specific compounds, including flavonoids, alkaloids, steroids, and phenolic compounds. Antioxidant activity was assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay with different solvents (aqueous, ethanolic, and methanolic). Antimicrobial assays were tested against Staphylococcus aureus and Escherichia coli. Results: Sundried seeds (SDS) and peel (SDP) exhibited respective concentrations of 128 mg/ml and 141 mg/ml for flavonoids, 95 AE/g and 103 AE/g for alkaloids, 10.2 mg/ml and 9.6 mg/ml for steroids, and 170 GAE/g and 187 GAE/g for phenolic compounds.IC50 yield of SDS extracts exhibited in aqueous(5.84 ppm) and methanolic solvents(6.75 ppm), while SDP extracts showed moderate to strong activity in ethanol(47.71ppm) and methanol(84.50 ppm). Staphylococcus aureus inhibited the zone of 9 mm and 10mm and Escherichiacoli ruptured the membrane in 10 mm and 8 mm on both samples. Conclusions: Sundried seeds and peel from grapevine waste exhibited promising antioxidant and antimicrobial properties, promising further research for potential value-added applications.